Monepantel in cattle: pharmacokinetics and nematodicidal efficacy - Cantón, Candela (2020)
The increasing levels of resistance to all traditional anthelmintic classes have encouraged the search for molecules with alternative mechanisms of action. The broad-spectrum nematodicidal drug Monepantel (MNP) was initially developed to use in sheep. The goals of the work described here were to evaluate the pharmacokinetic (PK) behaviour and anthelmintic efficacy of MNP given to calves naturally infected with gastrointestinal nematodes (GIN) resistant to ivermectin (IVM) on two commercial farms. Thirty (30) male calves were randomly allocated into two groups (n= 15) and treated with either MNP orally at 2.5 mg/kg or IVM subcutaneously at 0.2 mg/kg. Eight animals from the MNP treated group (Farm 1) were randomly selected to perform the PK study. Drug concentrations were measured by HPLC. The efficacy was determined at 15 days after treatment by the FECRT. MNP and MNPSO2 were the main analytes recovered in plasma. MNPSO2 (measured in plasma up to 216 h post-treatment) systemic exposure was markedly higher compared to that obtained for MNP (measured up to 120 h post-treatment). Higher Cmax and AUC values were obtained for the active MNPSO2 metabolite (96.8 ± 29.7ng/mL and 9220 ± 1720ng.h/mL, respectively) compared to MNP (21.5 ± 4.62ng/mL and 1709 ± 651ng.h/mL, respectively). The MNPSO2 AUC value was 6-fold higher compared to the parent drug. Efficacies of 99% (Farm 1) and 96% (Farm 2) demonstrated the high efficacy of MNP (P< 0.05) against GIN resistant to IVM in cattle (reductions between 43 and 68% in both farms). While IVM failed to control Haemonchus spp. and Cooperia spp., MNP achieved 100% efficacy against Haemonchus spp., Cooperia spp. and Ostertagia spp. on both farms. However, MNP failed to control Oesophagostomum spp. (efficacies ranging from 22 to 74%). In conclusion, the oral treatment with MNP should be considered for dealing with IVM resistant parasites in cattle.